2020
DOI: 10.1037/emo0000561
|View full text |Cite
|
Sign up to set email alerts
|

Follow your gut? Emotional intelligence moderates the association between physiologically measured somatic markers and risk-taking.

Abstract: LISTA DE TABLASTabla 1. Datos sociodemográficos descriptivos en función del grupo de policonsumidores y no consumidores .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 120 publications
1
12
0
Order By: Relevance
“…Researchers have also shown that decision-makers who are able to understand emotions (Branch 3) take more efficient decisions as they are less influenced by irrelevant feelingssuch as incidental anxiety -which are unrelated to the decision at hand (Yip & Côté, 2013). More recently, these researchers have observed that decision makers with low EI tend to adopt maladaptive decision-making, due to their incorrect appraisal of intensity of physiological arousal (Yip et al, 2020).…”
Section: Relevance Of Ability Ei For Managersmentioning
confidence: 99%
“…Researchers have also shown that decision-makers who are able to understand emotions (Branch 3) take more efficient decisions as they are less influenced by irrelevant feelingssuch as incidental anxiety -which are unrelated to the decision at hand (Yip & Côté, 2013). More recently, these researchers have observed that decision makers with low EI tend to adopt maladaptive decision-making, due to their incorrect appraisal of intensity of physiological arousal (Yip et al, 2020).…”
Section: Relevance Of Ability Ei For Managersmentioning
confidence: 99%
“…Future research could fruitfully study some debiasing techniques to improve people’s emotional well-being. Furthermore, building on prior work linking emotions with decisions [45, 56–61], future research should investigate whether emotions are capable of debiasing judgmental errors.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has been mixed in the relative contribution of EI and IQ to performance on the IGT. Recent studies utilizing the MSCEIT has suggested that individuals low in EI tend to misappraise physiological signals in risk-taking (Yip et al, 2019), and perform poorly on the IGT, a "hot" task with physiological arousal of somatic markers in comparison to a decision-making task that was relatively cognitively "cool" and that did not tap affect (Checa and Fernández-Berrocal, 2019). Cognitive .…”
Section: Discussionmentioning
confidence: 99%